2018
DOI: 10.1186/s12974-018-1203-8
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 deletion ameliorates hypoglycemia-induced BBB permeability by inhibiting inflammatory responses

Abstract: BackgroundSevere hypoglycemia induces brain edema by upregulating aquaporin-4 (AQP4) expression and by degrading tight junctions. Acute severe hypoglycemia induces a proinflammatory environment that may contribute to a disruption in the epithelial barrier by decreasing tight junction protein expression. Interestingly, the altered AQP4 expression has been considered to play a critical role in neuroinflammation during acute brain injury. It has been shown that AQP4 deletion reduces brain inflammation in AQP4-nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Our data indicate that this upregulation of Aqp-4 is amplified in the SHRSP/FAD rat. A positive correlation between Aqp-4 and GFAP protein levels are consistent with prior reports of increased Aqp-4 corresponding with increased gliosis in a model of hypoglycemia (Zhao et al, 2018). Aqp-4 staining was redistributed to the neuropil, but it was unclear whether the loss of polarization was due to disintegration of vessels or retraction of endfeet.…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicate that this upregulation of Aqp-4 is amplified in the SHRSP/FAD rat. A positive correlation between Aqp-4 and GFAP protein levels are consistent with prior reports of increased Aqp-4 corresponding with increased gliosis in a model of hypoglycemia (Zhao et al, 2018). Aqp-4 staining was redistributed to the neuropil, but it was unclear whether the loss of polarization was due to disintegration of vessels or retraction of endfeet.…”
Section: Discussionsupporting
confidence: 91%
“…Quite remarkably, these AQP4-null mice show substantially improved outcomes and survivability over their wild-type counterparts in four models of CNS injury: ischemic stroke (Manley et al, 2000;Yao et al, 2015A;Hirt et al, 2017), water intoxication (Manley et al, 2000), bacterial meningitis (Papadopoulos and Verkman 2005), and spinal-cord compression (Saadoun et al, 2008). AQP4-null mice have also shown reduced CE and BBB permeability in a model of severe hypoglycemia (Zhao et al, 2018). These studies represent a genetic proof-of-principle highlighting the central role of AQP4 in the formation of cerebral edema and its potential as a target for an anti-edema strategy aimed at stroke therapy.…”
Section: Introductionmentioning
confidence: 96%
“…AQP4 is abundantly expressed in astrocytic endfeet processes in direct contact with blood vessels 7‐9 . The specific highly polarized expression of AQP4 was suggested to play critical roles in maintaining cerebral water balance and BBB integrity 10‐13 . Previous studies have reported that AQP4 polarity was disturbed in various neurological diseases that cause brain edema and BBB disruption 14‐17 .…”
Section: Introductionmentioning
confidence: 99%